Using leader affiliative humor to encourage employee knowledge sharing: The multilevel role of knowledge sharing self-efficacy and team psychological safety - Zhenting Xu; Jing Gong; Yiying Qu; Xiuming Sun (Journal of Innovation & Knowledge, 2023)
The aim of this study is to investigate the multilevel effect of leader affiliative humor on knowledge sharing behavior. Based on social information processing (SIP) theory, we frame a multilevel model of the effect of leader affiliative humor on employee knowledge sharing, focusing on the multilevel role of knowledge sharing self-efficacy and team psychological safety in the relationship between leader affiliative humor and employee knowledge sharing. By taking 286 responses (51 teams) as research samples, we adopt hierarchical linear model to test the proposed hypotheses. The results show that leader affiliative humor exerts positively direct and indirect effects on employee knowledge sharing via knowledge sharing self-efficacy, and team psychological safety, respectively. Moreover, team psychological safety positively moderates the relationship between knowledge sharing self-efficacy and employee knowledge sharing. These findings advance the literature by shedding light on whether, how, and when leader affiliative humor fosters employee knowledge sharing from the lens of SIP perspectives. Moreover, for organizations, this study highlights the central role of leader affiliative humor in fostering knowledge management and thereby innovation.